Confecção e utilização do aplicativo “eletro na mão” como ferramenta auxiliar para o ensino do eletromagnetismo - Batista, Francisco Bismak Freire (Universidade Federal Rural do Semi-Árido, 2020)
The influence of technologies on the life of modern man, especially with the use of smartphones and tablets, grows daily making us increasingly dependent of your use. On the other hand, the use of these tools in the classroom is still a taboo and not accompanies the technological development in our society. Seeking to insert the use of technology as an additional teaching tool, the application “Eletro na Hand” that addresses the main contents of electromagnetism taught in high school, using a simple, dynamic and attractive language. Aiming at the importance of stimulating the physics teaching through the use of electronic devices, stimulating the teaching-learning process so that the student becomes the protagonist of their learning. The elaboration and construction of the application was made on the Fábrica de Applications platform, and cover topics of physics as Introduction to Electricity, Electric Field, Electric Current, Electric Potential and Magnetic Field, subjects usually covered in the third grade of high school. For test the effectiveness of the application we developed and applied a didactic sequence based on in the kellyan learning cycle. After application of the product, results show that there was greater interest from students when the application was used, they showed more motivated and stimulated in the teaching-learning process
Keywords: Aplicativo; Física; Tecnologias; Eletromagnetismo; Application; Physics; Technologies; Electromagnetism; CIENCIAS EXATAS E DA TERRA::FISICA